Penerapan Sanksi Pidana Mati terhadap Pelaku Pembunuhan Berencana Disertai Mutilasi sebagai Upaya Pemenuhan Keadilan, Kemanfaatan dan Kepastian Hukum - Inarotul Insyaniyah (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
Along the times the number of crimes that occur in Indonesia is currently increasing. This crime is certainly caused by many factors whether it is from human’s self or from the rapid technology that shows the varied practices of crimes that community can imitating the pattern of crime which can be very cruel crimes such as murder accompanied by mutilation. Provisions murder or premeditated murder have been regulated in the Indonesian Criminal Code (KUHP) in book II regarding Crimes articles 338-340, if the murder is premeditated murde then the perpetrator will be threatened with a maximum sanction of the death penalty.